Spinal Cord Excitability and Sprint Performance Are Enhanced by Sensory Stimulation During Cycling - Pearcey, Gregory E. P.; Noble, Steven A.; Munro, Bridget; Zehr, E. Paul (Frontiers in Human Neuroscience, 2017)
Spinal cord excitability, as assessed by modulation of Hoffmann (H-) reflexes, is reduced with fatiguing isometric contractions. Furthermore, spinal cord excitability is reduced during non-fatiguing arm and leg cycling. Presynaptic inhibition of Ia terminals is believed to contribute to this suppression of spinal cord excitability. Electrical stimulation to cutaneous nerves reduces Ia presynaptic inhibition, which facilitates spinal cord excitability, and this facilitation is present during arm cycling. Although it has been suggested that reducing presynaptic inhibition may prolong fatiguing contractions, it is unknown whether sensory stimulation can alter the effects of fatiguing exercise on performance or spinal cord excitability. Thus, the aim of this experiment was to determine if sensory stimulation can interfere with fatigue-related suppression of spinal cord excitability, and alter fatigue rates during cycling sprints. 13 participants randomly performed three experimental sessions that included: unloaded cycling with sensory stimulation (CONTROL + STIM), sprints with sensory stimulation (SPRINT + STIM), and sprints without stimulation (SPRINT). Seven participants also performed a fourth session (CONTROL), which consisted of unloaded cycling. During SPRINT and SPRINT + STIM, participants performed 7, 10s cycling sprints interleaved with 3min rest. For CONTROL and CONTROL + STIM, participants performed unloaded cycling for ~30min. During SPRINT + STIM and CONTROL + STIM, participants received patterned sensory stimulation to nerves of the right foot. H-reflexes and M-waves of the right soleus were evoked by stimulation of the tibial nerve at multiple time points throughout exercise. Sensory stimulation facilitated soleus H-reflexes during unloaded cycling, whereas sprints suppressed soleus H-reflexes. While receiving sensory stimulation, there was less suppression of soleus H-reflexes and slowed reduction in average power output, compared to sprints without stimulation. These results demonstrate that sensory stimulation can substantially mitigate the fatiguing effects of sprints.